Racial and Ethnic Disparities in Preventive Service Use Among Adults Before and During the COVID-19 Pandemic - Lisa Dubay PhD; Fredric E Blavin PhD; Laura Barrie Smith PhD; Julianna Carlyn Long BSPH (SAGE Publishing, 2024)
Our objective was to assess changes in preventive services use before and during the COVID-19 pandemic. We obtained secondary survey data from the National Health Interview Survey for 2019 and 2021. We examined, six preventive services among all adults. Descriptive and multivariate analyses assessed changes in preventive service use among adults and by race/ethnicity for 2019 and 2021 (drawing from an unweighted sample of 60 843 weighted to be 386.2 million across both years). We used Ordinary least squares estimation to conduct a difference-in-differences analysis that assessed changes in service use for non-white racial/ethnic groups relative to changes for white non-Hispanic adults between 2019 and 2021. We found preventive services use declined overall for each screening service assessed. Asian adults experienced the largest declines relative to white adults for "well visit within the last year" (−7.45 percentage points (pp) relative to white adults), "blood pressure screening within the last year" (−7.85 pp), and "mammograms within the last year" (−12.3 pp). While adults in other racial/ethnic groups did not experience significant declines in preventive services use relative to white adults between 2019 and 2021, pre-existing disparities remained for Hispanic and American Indian/Alaska Native (AIAN) adults compared to white adults. In conclusion, preventive service use declined in the first years of the COVID-19 public health emergency, and existing disparities in access for Hispanic and AIAN adults continued. Future research should investigate barriers Asian adults may face in obtaining access to preventive services after the conclusion of the public health emergency and federal pandemic-related protections.